Analisis Sistem Informasi Akuntasi Pembelian Dan Penjualan Pada PT. Niaga Redja Abadi Tasikmalaya (Bengkel AHASS Niaga Redja Abadi) - Shofa, Gina Kamila; Indriani Pratami, Eggi (EKOBIMA, 2024)
The purpose of this study was to analyze the implementation of the buying and selling accounting information system at the AHASS Niaga Redja Abadi Motor Workshop by using the theory of PIECES analysis. This theory is used to identify problems in accounting information systems that are implemented based on several aspects, namely performance, information, economy, security, efficiency and customer service. Redja Abadi's AHASS Commercial Workshop was chosen as the object of this study. Implementation of buying and selling SIA at the AHASS Niaga Redja Abadi Workshop on the six aspects used, three of which were assessed as meeting the PIECES theory standards. Aspects that are considered to have met the standards are aspects of performance, control and customer service, while those that have not met the standards are economic, information and efficiency aspects.